THE MEDIATING ROLE OF FINANCIAL ATTITUDE IN LINKING FINANCIAL CAPABILITY AND DEBT DECISION AMONG INFORMAL WOMEN ENTREPRENEURS - Andini Ekasari; Meutia; Lia Uzliawati; Windu Mulyasari (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyse the influence of financial knowledge, financial attitudes, and financial behaviour on the debt decision of informal women entrepreneurs in Indonesia. By delivering questionnaires and quantitative methodology. 279 respondents were collected, and the results could be processed with SmartPLS Structural Equation Modelling (SEM). This paper explores the relationship between financial inclusion, financial literacy, and the important role of financial attitudes in improving decision-making skills related to debt management. At the same time, financial inclusion and financial literacy are essential, but not enough to encourage healthy debt practices. A constructive financial attitude emerges as an important determinant, contributing to understanding and implementing prudent debt decisions women in the informal sector. This research provides practical contributions for governments, financial institutions, and cooperatives in designing gender-responsive financial literacy programs. The findings advance the Theory of Planned Behavior in financial decision-making and provide actionable guidance for designing gender-responsive financial capability programs.